Seksmisja - Machulski, Juliusz (Poland : Sadowski, Piotr, 1984)
A “cathartic” film watched by nearly 13 million Poles just after Martial Law ended. Two scientists are chosen as guinea pigs, placed in hibernation to be brought back to life after three years. In the meantime, however, World War III breaks out and wipes out nearly everything. When they wake up, it turns out that that they are the only living specimens of the male sex in a new, underground society composed exclusively of women. Max used to be woman-chaser so he finds himself in heaven. Albert, on the other hand, forgot all about love and sex as a serious scientist, but is willing to learn. So are the Amazons, who after a kiss turn into pliant kittens. The Council of Women is going to decide the men's fate, so they are trying to win time. Eventually they make it to the surface where – as it turns out – there is life and somebody is manipulating life underground. It is a cult comedy, recently criticized by feminist authors for its latent sexism and for portraying the anti-communist struggle as an exclusively male domain.
Duration: 01:56:00
Keywords: Fiction films